Investigation of the association between the triglyceride-glucose index and the incidence of frailty among middle-aged and older adults: evidence from the China health and retirement longitudinal study - Long, Qingwen; Li, Yongli; Shi, Zijuan; Lee, Yujun; Mao, Lifang (Frontiers in Public Health, 2025)
AimLimited researches have investigated the association between the Triglyceride-glucose index (TyG) and frailty vulnerability in middle-aged and older Chinese populations. This study aims to strengthen the scientific foundation for frailty prevention and management by analyzing the correlation between TyG and frailty, ultimately providing more targeted intervention strategies.MethodsThis study included middle-aged and older individuals who participated in the China Health and Retirement Longitudinal Study (CHARLS) from 2015. A multiple logistic regression model was constructed to assess the correlation between the TyG index and frailty. Additionally, restricted cubic spline (RCS) analysis was employed to evaluate the dose–response correlation between the two variables.ResultsAmong the 3,978 participants included in the study, 667 individuals (16.8%) were identified with frailty. After adjusting for multiple factors in a logistic regression model, it was determined that individuals in the highest quartile group of the TyG index had a 1.43 times higher risk of frailty compared to those in the lowest quartile group (OR = 1.43, 95% CI: 1.10 1.85, p = 0.007). The RCS analysis further revealed a positive dose–response relationship, indicating that a higher TyG index was associated with an increased risk of frailty in middle-aged and older adults.ConclusionResearch has shown a significant positive linear relationship between an increased TyG index and a higher prevalence of frailty in middle-aged and older individuals. Elevated TyG index levels could signal an increased vulnerability to frailty among individuals.